O bairro de Ma¯dina Ya¯bura - Filipe, Vanessa (2013)
As intervenções arqueológicas desenvolvidas no espaço do actual Museu Municipal de Évora foram realizadas nos anos de 1996 e 1997 pela empresa de arqueologia Arkhaios em estreita colaboração com Theodor Hauschild e o Instituto Arqueológico Alemão. A abordagem arqueológica centrada nos níveis de ocupação islâmica permitiu o desvelar de informações sobre o legado civilizacional islâmico em Évora, nomeadamente o processo de urbanização do bairro residencial situado no interior de ma¯dina Ya¯bura. The archaeological interventions developed in the space of the current Municipal Museum of Évora were performed in the years 1996 and 1997 by the company of archeology Arkhaios in close collaboration with Theodor Hauschild and the German Archaeological Institute. The archaeological approach centered on the levels of islamic occupation has allowed the unveiling of information about the Islamic civilization legacy in Évora, in particular the process of urbanization of the residential neighborhood located in the interior of ma¯dina Ya¯bura.